Association Between Trust in Health Care Professionals and Health Care Access: Insights From an Online Survey Across 21 Countries - Louisa Ewald; John Bellettiere; Tamer H. Farag; Kristina M. Lee; Sidhartha Palani; Emma Castro; Amanda Deen; Catherine W. Gillespie; Bethany M. Huntley; Alison Tracy; Anna-Carolina Haensch; Frauke Kreuter; et al. (International Journal of Public Health)
ObjectivesThis study evaluates the association between trust in health care professionals and health care delays across 21 countries.MethodsWe apply logistic regression models to survey data of over 621,000 individuals collected in Spring 2023.ResultsResults show 44.5% of respondents with medical conditions experienced delays in accessing health care and 44.1% reported lack of trust in health care professionals. Those who trusted health care professionals had significantly lower odds of delaying medical care. Trust was most strongly associated with delays in the United Kingdom (OR = 0.373, 95% CI = 0.273–0.510), while South Africa had the smallest association (OR = 0.762, 95% CI = 0.582–0.997).ConclusionTrust is important in influencing health care-seeking behaviors, though the causal direction warrants further research. There is a need for targeted strategies to build and sustain trust in health care relationships as well as enhancing health care access.